DIPLOMASI PUBLIK INDONESIA DALAM UPAYA PENINGAKATAN PARIWISATA MELALUI KAMPANYE WONDERFUL INDONESIA ERA PRESIDEN JOKO WIDODO (Studi Kasus: TheJakartaPost.com 2015-2019) - Razdkanya Ramadhanty (UIR Press, 2020)
This research discusses how Indonesian public diplomacy through the Wonderful Indonesia campaign as an Indonesian tourism brand, is able to attract the interest of foreign tourists and provide a positive influence for Indonesia.Public diplomacy is a policy that includes power, especially those that related to soft power and do not directly influence as well as culture, values and ideology. One of the public diplomacy carried out by the government of President Joko Widodo 2014-2015 is the 'Wonderful Indonesia' campaign which is an Indonesian tourism brand. In realizing President Joko Widodo's nawacita, which makes tourism a leading sector, the Ministry of Tourism has a variety of public diplomacy implementations in launching the Wonderful Indonesia campaign. Online media have recently been considere as one of the most effective media in spreading information to various parts of the world, making it useful for Indonesia to spread policies and information related to ‘Wonderful Indonesia’ and the development of Indonesian tourism. One of the online media that has international readers is thejakartapost.com. As an English-language daily from Indonesia, thejakartapost.com has the ease of disseminating information through an Indonesian perspective.